Nutrient Utilization and Growth Performance of Jalauni Lambs Grazed on ThreeTier Silvipasture System - M. M. Das; S. N. Ram; R. V. Kumar (Indian Journal of Animal Nutrition, 2025)
Seasonal variation in chemical composition as well as nutrient utilization and growthperformance of Jalauni lambs were studied under grazing on three tier silvipasture consisting(stocking rate of 2ACU/ha) of grass (C.ciliaris),legume (S.seabrana), shrubs (Z.xylopyrus,Z.mauritiana, A.Catechu) and tree (Hardiwickia binata) during growing (August-October) aswell as post-growing (November-January) seasons in Bundelkhand region along withsupplementation (1% of body weight) of concentrate mixture. Average dry matter (DM) contentof pasture forages increased with advancement of maturity from 42.89% during growing seasonto 52.59% in post growing season, with concomitant increase in neutral detergent fiber (NDF)content from 57.67% to 61.36%, and reduction in crude protein(CP) content from 11.55% to8.64%. DM intake was significantly (P<0.05) higher in growing than post growing season.Similarly, digestibility of nutrients namely DM, OM, NDF and CP were higher in growingseason than post growing season. Intake (g/W0.75) of digestible crude protein (DCP) was higher(6.15) in September as compared to December (3.74). Metabolizable energy (ME) intake (kj/W0.75 ) also followed the same trend. Daily live weight gain (g/d) was also significantly (P<0.05)higher in growing season than post growing season. It was concluded that nutrient intake,nutrient utilization and growth performance were significantly (P<0.05) affected during postgrowing season due to deterioration of nutritive value of available pasture biomass which wasreflected from lower digestible nutrient intake and body weight gain in Jalauni lambs